Nitrogen Reduction Reaction: Heteronuclear Double‐Atom Electrocatalysts. Issue 4 (17th January 2023) - Wang, Yuanzhe; Wang, Jing; Li, Heen; Li, Yaguang; Li, Junkai; Wei, Kuo; Peng, Fei; Gao, Faming
Abstract : Heteronuclear dual‐site catalysts (HDACs), inspired from single‐atom catalyst, have been proposed as advanced alternatives of noble metal catalyst, especially toward nitrogen reduction reaction (NRR). However, the search for favorable candidates with both promising NH3 yield and noble Faradaic efficiency is still challenging, due to limited experimentally available bi‐metal pairs and lack of thorough understanding of the design criteria. Herein, by theoretical screening of a family of M/Fe combinations (M = Sc, Ti, V, Cr, Mn, Co, and Ni), atomically dispersed binary V/Fe architecture anchored on nitrogen‐doped carbon matrix (VFe/NC) is proposed with a small limiting potential (0.39 V) and high selectivity over the hydrogen evolution reaction (HER). Owing to a perfect matching with N2 antibonding state, V 3 d z 2 orbitals, "push" electrons into adsorbed N2 antibonding stats and simultaneously Fe 3 d yz "pull" extra electrons back. Benefiting from the synergistic effect from the dual‐active sites, an outstanding NH3 yield of 73.44 μg h −1  mgcat −1 (8070.32 μg h −1  mgVFe −1 ) and an excellent Faradaic efficiency of 43% are achieved, overwhelming literature‐reported atomic‐level catalysts. This study promotes the development of HDACs that are capable of high yield rate accompanied with high Faradaic efficiency. Abstract : It is apparent that the two‐site acceptance–donation process is more effective to promote the "push–pull" mechanism, which contributes to the promotion of nitrogen reduction reaction activity.